Peter Mankowski, Research Handbook on the Brussels I bis Regulation - Suderow, Juliana (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
Este artículo reseña: Peter Mankowski, Research Handbook on the Brussels I bis Regulation, Edward Elgar Publishing, Cheltenham/Northampton 2020, nr de páginas 392, ISBN: 9781788110785